The Effect of Purification Units for Drinking Water Spread in Al-Alam and Al-Bu Ajil on Heavy Metals - Amjad Abdel-Latif Ahmed Alluhaiby; Saadat Mustafa; Shaima Fateh (International Journal for Research in Applied Sciences and Biotechnology, 2021)
The current study was carried out on the treatment and treatment units located in the district of Al-Alam and the village of Al-Bu Ajil, which are located near the Tigris River, with two stations for each region for the period from September 2020 to February 2021, as two samples were collected for each treatment unit by a sample before treatment and a sample after treatment. Iron values ​​ranged between (0-0.9) mg / liter before and after treatment, and they ranged between (0-0.05) mg / liter, and zinc values ​​were recorded values ​​ranging between (0-0.9) mg / liter. Before treatment and after treatment, it ranged between (0-0.05) mg / liter, while the aluminum values ​​were relatively few, as values ​​ranged between (0.03_0) mg / liter. As for the values ​​after treatment, they were (0) mg / liter. Cadmium values ​​were between (0,1_0) mg / liter. In the samples after treatment also, all values ​​were (0) mg / liter in all stations, and the nickel values ​​ranged between (0,9_0) mg / liter in the samples before treatment and after treatment. The values ​​were all (0) mg / liter in both stations, and the copper values ​​were very low in the mentioned areas, as values ​​ranged between (0.1_0) mg / liter before treatment and after treatment, the values ​​were (0) mg / liter. In both stations, the purification plants proved their high efficiency in filtering water from heavy elements, and the samples after treatment were in conformity with the Iraqi standards for drinking water. It is worth noting that the purification plants in the areas of Al-Alam and Al-Bu Ajil need a constant monthly maintenance and a replacement process for the filters as they draw their water from wells.